P168 Influence of first-line treatment for epithelial ovarian cancer on the immune system. (1st November 2019) - Baert, T; Landolfo, C; Ceusters, J; Thirion, G; Van Hoylandt, A; Verschuere, T; Van Rompuy, A-S; du Bois, A; Timmerman, D; Vergote, I; Coosemans, A
Abstract : Introduction/Background: The KEYNOTE-021 trial showed a beneficial effect of the combination of chemotherapy and immunotherapy in non-small-cell lung cancer, since then multiple trials have studied combination of chemotherapy and immunotherapy. However, not all combinations yield positive results, as we learned from the JAVELIN Ovarian 200 trial. Therefore, we need to gain insight into the effect of chemotherapy on the immune system in vivo . In the current study, we investigated the influence of first-line treatment for ovarian cancer on the immune system. Methodology: Tumour biopsies and peripheral blood mononuclear cells were collected prospectively in 43 patients with epithelial ovarian cancer. Samples were taken at diagnosis, after cytoreductive surgery, after three courses of (neo-)adjuvant chemotherapy and at the end of their primary treatment. Immunostimulatory cells (Thelper cells (Th), Tcytotoxic cells (Tc), natural killer cells (NK)) and immunosuppressive cells (regulatory T cells (Treg), mMDSC (monocytic myeloid-derived suppressor cells), gMDSC (granulocytic MDSC)) were measured in blood using fluorescence activated cell sorting. Additionally, we checked for the expression of activation markes and immune checkpoint molecules on immune cells. On tumour biopsies, we performed immunohistochemistry for Tc and Treg. Results: First-line treatment led to a significant increase in Tc in circulation (p<0.05). During neoadjuvant chemotherapy we observed an increase in Tc in the tumour and in blood (p<0.05 and p<0.01 respectively). In addition, we observed an increased expression of PD-1 on all circulating T cells during neoadjuvant chemotherapy. Chemotherapy after (interval)debulking surgery led to an overall increase in immunosuppressive cells (Treg (p=0.0001) and mMDSC (p<0.05)) and a higher expression of PD-1 and CTLA4 on circulating T cells. Conclusion: We observed a clear change in the immune phenotype of patients during first-line treatment for epithelial ovarian cancer. Chemotherapy led to an increase in the expression of immune checkpoint markers on Th, Tc and Treg in blood. Disclosure: TB has reported research grant from Amgen, travel expenses from Amgen and Roche as well as advisory board membership for Tesaro. IV has performed contracted research for Oncoinvent AS and Genmab, received research grants from Amgen, Roche, Stichting tegen Kanker, received travel expenses from Takeda Oncology, Pharma Mar, Genmab, Roche, Astrazeneca, Tesaro, Clovis, Immunogen and is a advisory board member for Advaxis, Inc., Eisai Inc., MSD Belgium, Roche NV, Genmab, F. Hoffmann-La Roche Ltd, Pharmamar, Millennium Pharmaceuticals, Clovis Oncology Inc., AstraZeneca NV, Tesaro, Oncoinvent AS, Immunogen Inc and Sotio. CL, JC, GT, AVH, TV, A-SVR, AdB, DT and AC have no disclosures concerning this abstract.